REVEALING THE TRENDS: STUDENTS' MOTIVATIONS FOR CHOOSING ENGLISH CAPTIONS ON INSTAGRAM - Elsa Amelia Fitri; Burhanudin Rais; Asni Tri Hartati (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2023)
Instagram is now a worldwide photo and video-sharing social media platform, and English is increasingly used in captions by non-English speaking Instagram users. With this known, this study aimed to determine the students' reason at Universitas Kapuas using English as a caption on Instagram. This study involved 22 students of Universitas Kapuas. The research design used was a qualitative descriptive. Data collection used an interview consisting of five questions. The researchers also used observation to triangulate the data. The results of this study stated that students use English captions on Instagram, which were influenced by intrinsic and extrinsic factors. The results showed that intrinsic factor was the highest. More than 50% of the students or participants used the intrinsic factor in writing English caption. The intrinsic factor included was the need for learning English. While for extrinsic motivation, the respondents mentioned that using English as a caption looks cool and aesthetic.